(untitled) (Texas Journal of Philology, Culture and History, 2024)
Ghafur Ghulam is considered the greatest figure in Uzbek literature within the works of Navoiy. His poems and writings hold significant national and spiritual value, contributing greatly to literature. The legacy of Navoiy highlights his importance in literature and the uniqueness of his created works